O usuário, a família e a equipe de saúde: a quem a vida pertence? uma pesquisa avaliativa sobre as intervenções para uma morte digna no Hospital Universitário Walter Cantídio - HUWC - Brito, Amalia Claudia Facundo de (2022)
It was through the Health Reform Movement, initiated in the 1970s, that health became recognized as a citizenship right, guaranteed in the Constitution promulgated in 1988. This legal framework provided great advances in the development of health policy, among them is Law 8080/1990, which regulates the right to health in the national territory, which is so important to human dignity. Amid the advancement of medicine and the control of chronic and degenerative diseases, as well as the use of technology, more and more specialized medications, treatments and procedures capable of providing longevity are emerging. However, it is clear that science fights a constant battle with death, as if it were not part of life, becoming feared by everyone in contemporary times. Given this scenario, the Palliative Care approach becomes important in monitoring patients with diseases that threaten their quality of life, including their families, at various stages, from the diagnosis of the disease. The study presented has as its starting point the guarantee of the right to a dignified death for patients with a life-threatening disease, care centered on the person and not the disease. Based on the experience lived in the Palliative Care service at the Walter Cantídio University Hospital, the research was directed to cases of hospitalized patients, regardless of diagnosis and age group. Although it is expected that palliative care is only for people in finitude, anyone, regardless of the diagnosis, may benefit from follow-up. Using a qualitative approach with quantitative input, based on bibliographical research and semi-structured interviews, this research sought to analyze the interventions of HUWC health professionals to guarantee a dignified death for patients monitored by Palliative Care. Considering this scenario, it is pointed out that the development of the main discussions are present in the articulation between the categories death, palliative care, intersectorality and public policies from an evaluative perspective. It was possible, in this research, to circumscribe a rich material with different positions being complementary, in in relation to the perception of workers and family members about the palliative approach